Tailoring size and release kinetics of ?/?-hybrid carrageenan microgels via a surfactant-assisted technique - Rodriguez S. (2021)
The Vice-Rectorate for Research (VRI-PUCP) of the Pontificia Universidad Catolica del Peru and the National Council of Science, Technology and Technological Innovation (CONCYTEC-FONDECYT) are greatly acknowledged for financial support. The Institute of Polymer Science and Technology of the Spanish Council for Scientific Research (ICTP-CSIC, Madrid, Spain) is acknowledged for experimental assistance.